Analysis of Learning Outcomes Through Audiovisual Learning Media for PJOK Subjects with Healthy, Nutritional and Balanced Eating Patterns for Junior High School Students - Syifa Wulan Alfiani; Bertika Kusuma; Agus Wiyanto; Suprapti (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
This research aims to analyze the effectiveness of audiovisual learning media on student learning outcomes in Physical Education, Sports and Health (PJOK) subjects with material on healthy, nutritious and balanced eating patterns in class VII SMPN 37 Semarang. Using a pre- experimental research design with a pretest-posttest one group design model, this research involved several students as samples. Data was collected through learning outcomes tests that had been validated by material experts and analyzed using descriptive and inferential statistics with the t-test. The research results show that the use of creative and interesting audiovisual learning media significantly improves student learning outcomes compared to conventional methods. This media makes it easier for students to understand the material, increases interest in learning, and allows flexible learning access.